Envolvimento de mecanismos dopaminérgicos na atividade antidepressiva da leptina no comportamento tipo-depressão induzido por LPS em camundongos - Cordeiro, Rafaela Carneiro (2014)
Depression is a chronic and recurrent disorder, whose prevalence in the general population is between 3-11%, being highly disabling and associated with increased morbidity due to medical reasons and risk of suicide. The discovery of new antidepressants with different action mechanisms is expected, with the hope that there is an increase in remission rates associated with the pharmacological treatment of depression. Leptin was first described as an anti-obesity hormone and later the expression of the long form of the leptin receptor in limbic structures related to mood regulation was discovered. Studies in humans suggest its involvement in the pathophysiology of depression. The action of leptin in the forced swimming test resembles those described for antidepressants, so it is possible that the cognate receptors of dopamine (DA) involved in the pathophysiology of depression are involved in the antidepressant activity of leptin. Thus, the present study investigated the involvement of DA and its receptors (D1 and D2-like) in animals subjected to immune challenge by systemic administration of LPS (0.5 mg / kg, ip). To do so we evaluated the behaviors related to depression: forced swimming, locomotor activity and preference for sucrose, 24 h after administration of endotoxin, respectively, key time-point for the development of depressive-like behaviors. Neurochemical analyzes were also done by evaluating the levels of lipid peroxidation (TBARS), reduced glutathione (GSH), IL-1 β and BDNF in brain areas: prefrontal cortex, hippocampus and striatum. The results showed that 24 hours after the administration of LPS there was an increase of immobility in the forced swimming test, reduction of sucrose preference and no change in open field when compared to control animals, featuring a depression-like behavior induced by this endotoxin. Leptin was able to restore the behaviors altered by LPS similar to the control levels. In neurochemical changes there was a decrease of GSH levels in all brain areas studied in animals treated with LPS, increased lipid peroxidation and IL-1β, which is related to oxidative and inflammatory hypothesis of depression. Leptin treatment was able to prevent the LPS-induced changes in IL-1β levels in the prefrontal cortex and striatum and increase BDNF levels in hippocampus, similar to Imipramine. These findings show that in this model, the antidepressant mechanism of leptin involves a possible anti-inflammatory effect of this hormone.